The Making of Religious Policy, 1533–1546: Henry VIII And The Search For The Middle Way - Bernard, G. W. (The historical journal, 1998)
Too often religious policy in Henry VIII's reign after the break with Rome has been seen as fluctuating and inconsistent as he was influenced first by one group of ministers and courtiers and then by another. Here it is argued by contrast that Henry VIII was very much the dominant force in the making of religious policy and that his policy, which he pursued skilfully and consistently, is best characterized as a search for the middle way.